BiG-FAM: the biosynthetic gene cluster families database. Issue Volume 49:Issue D1(2021) (3rd October 2020) - Kautsar, Satria A; Blin, Kai; Shaw, Simon; Weber, Tilmann; Medema, Marnix H
Abstract: Computational analysis of biosynthetic gene clusters (BGCs) has revolutionized natural product discovery by enabling the rapid investigation of secondary metabolic potential within microbial genome sequences. Grouping homologous BGCs into Gene Cluster Families (GCFs) facilitates mapping their architectural and taxonomic diversity and provides insights into the novelty of putative BGCs, through dereplication with BGCs of known function. While multiple databases exist for exploring BGCs from publicly available data, no public resources exist that focus on GCF relationships. Here, we present BiG-FAM, a database of 29, 955 GCFs capturing the global diversity of 1, 225, 071 BGCs predicted from 209, 206 publicly available microbial genomes and metagenome-assembled genomes (MAGs). The database offers rich functionalities, such as multi-criterion GCF searches, direct links to BGC databases such as antiSMASH-DB, and rapid GCF annotation of user-supplied BGCs from antiSMASH results. BiG-FAM can be accessed online at https://bigfam.bioinformatics.nl . Graphical Abstract: